Routledge handbook of athlete welfare - Lang, Melanie (Routledge international handbooks, 2021)
Athlete welfare should be of central importance in all sport. This comprehensive volume features cutting-edge research from around the world on issues that can compromise the welfare of athletes at all levels of sport, and on the approaches taken by sports organisations to prevent and manage these. In recent years, sports organisations have increased their efforts to assure athlete health, safety, and well-being, often prompted by high-profile disclosures of sexual, physical and emotional abuse, bullying, discrimination, disordered eating, addiction, and mental health issues. In this book, contributors lift the lid on these and other issues that jeopardise the physical, emotional, psychological, social, and spiritual welfare of athletes of all ages to raise awareness of the broad range of challenges athletes face. Chapters also highlight approaches to athlete welfare and initiatives taken by national and international sport organisations to provide a safer, more ethical sports environment. As the first book to focus exclusively on athlete welfare, this is an essential read for students and researchers in sports studies, coaching, psychology, performance, development and management, and physical education. It is also a useful reference point for anyone working in welfare, safeguarding, child protection, and equity and inclusion in and beyond sport